Enzymatic Regulation of the Gut Microbiota: Mechanisms and Implications for Host Health - Zipeng Jiang; Liang Mei; Yuqi Li; Yuguang Guo; Bo Yang; Zhiyi Huang; Yangyuan Li (Biomolecules)
The gut microbiota, a complex ecosystem, is vital to host health as it aids digestion, modulates the immune system, influences metabolism, and interacts with the brain-gut axis. Various factors influence the composition of this microbiota. Enzymes, as essential catalysts, actively participate in biochemical reactions that have an impact on the gut microbial community, affecting both the microorganisms and the gut environment. Enzymes play an important role in the regulation of the intestinal microbiota, but the interactions between enzymes and microbial communities, as well as the precise mechanisms of enzymes, remain a challenge in scientific research. Enzymes serve both traditional nutritional functions, such as the breakdown of complex substrates into absorbable small molecules, and non-nutritional roles, which encompass antibacterial function, immunomodulation, intestinal health maintenance, and stress reduction, among others. This study categorizes enzymes according to their source and explores the mechanistic principles by which enzymes drive gut microbial activity, including the promotion of microbial proliferation, the direct elimination of harmful microbes, the modulation of bacterial interaction networks, and the reduction in immune stress. A systematic understanding of enzymes in regulating the gut microbiota and the study of their associated molecular mechanisms will facilitate the application of enzymes to precisely regulate the gut microbiota in the future and suggest new therapeutic strategies and dietary recommendations. In conclusion, this review provides a comprehensive overview of the role of enzymes in modulating the gut microbiota. It explores the underlying molecular and cellular mechanisms and discusses the potential applications of enzyme-mediated microbiota regulation for host gut health.